2022
DOI: 10.3390/cancers14071759
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma Tumor Origin: A Guide for Personalized Medicine

Abstract: Lung adenocarcinoma, the major form of lung cancer, is the deadliest cancer worldwide, due to its late diagnosis and its high heterogeneity. Indeed, lung adenocarcinoma exhibits pronounced inter- and intra-tumor heterogeneity cofounding precision medicine. Tumor heterogeneity is a clinical challenge driving tumor progression and drug resistance. Several key pieces of evidence demonstrated that lung adenocarcinoma results from the transformation of progenitor cells that accumulate genetic abnormalities. Thus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 100 publications
0
49
0
Order By: Relevance
“…Although there are several therapeutic options for lung cancer, including surgery, chemotherapy, radiotherapy and targeted therapy, the overall prognosis is still far from satisfactory, with a 5-year survival rate about 19% [ 3 5 ]. The difficulty in treating LUAD is mostly due to the high heterogeneity of LUAD [ 6 ]. Therefore, exploring more efficient biomarkers is crucial for diagnosis, prognosis, and risk assessment of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several therapeutic options for lung cancer, including surgery, chemotherapy, radiotherapy and targeted therapy, the overall prognosis is still far from satisfactory, with a 5-year survival rate about 19% [ 3 5 ]. The difficulty in treating LUAD is mostly due to the high heterogeneity of LUAD [ 6 ]. Therefore, exploring more efficient biomarkers is crucial for diagnosis, prognosis, and risk assessment of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high incidence of resistance to radiotherapy and immunotherapy has contributed to unfavorable clinical outcomes for patients. Lung cancer is a highly heterogeneous tumor, and its occurrence is the result of coregulation of multiple genes [ 5 ]. In-depth investigation of the molecular mechanism of LUAD will provide valuable guidance for early diagnosis and individualized treatment of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…The initial symptoms of LUAD are often not obvious, and by the time the disease becomes apparent, it is already in an advanced stage. LUAD is treated with radiotherapy, chemotherapy, immune checkpoint inhibitor therapy, and molecular targeted therapy, of which molecular targeted therapy has achieved excellent results in recent years but is prone to treatment resistance ( Drosten and Barbacid, 2022 ; Seguin et al, 2022 ). Lung cancer is often accompanied by abnormal expression of multiple genes, and recent studies have indicated that multigene-targeted treatments have favorable therapeutic effects ( Piñeiro-Yáñez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%